PENGEMBANGAN MODUL PEMBELAJARAN IPA MELALUI PENERAPAN TEORI ELABORASI DI SMP NEGERI 2 PONTIANAK - Herdiana, Yudi; Radiana, Usman; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe limitations of learning media result in less satisfying learning outcomes. This encourages researchers to carry out development research with a focus on developing learning modules to achieve learning outcomes of concepts and solving problems in the human reproductive system. Research questions are how module development is carried out, elaboration of learning material, module display and student responses. The research method used is a qualitative method with research subjects being 9th grade students in SMP Negeri 2 Pontianak 2017/2018 Academic Year. The module development process involves media experts and material experts to provide an assessment of the module before being evaluated and tested. Data collection techniques in this study are observation, interviews and learning outcome tests. The results of the module evaluation include material aspects, presentation and language by media experts 76.57 (good). and material expert 83.52 (very good). The response of students to the modules developed in the form of learning outcomes in individual trials and limited trials showed that 100% of students achieved completeness. Furthermore, the learning outcomes of 36 students during field trials were 32 students or 88.89% achieved completeness. Thus the learning modules developed are suitable for use in learning.Â Keywords : Research of Development, Learning Module, Elaboration Theory